Lexical level and restricted vocabulary: dialectisms, specialized vocabulary, and archaisms (on the example of Uzbek and English languages) - Sobirova, Zarnigor (The Lingua Spectrum, 2025)
The article systematically examines the lexical level of language on the basis of three main principles – morphological, semantic, and stylistic criteria. The nature, scope of use, and functional characteristics of restricted vocabulary (dialectisms, specialized vocabulary – jargon, argot, terms – as well as archaic and obsolete units) are analyzed through the examples of Uzbek and English languages. The research relies on theoretical literature, explanatory dictionaries, and authentic speech samples; the descriptive, comparative, and componential approaches were integrated as the methods of analysis. The results demonstrate that the boundaries between groups in the lexical system are dynamic, and that stylistic requirements, alongside social and regional factors, exert a strong influence on the realization of lexical units.